SISTEM PENGELOLAAN LIMBAH PADAT B3 DI RUMAH SAKIT MUHAMMADIYAH BABAT KABUPATEN LAMONGAN - Amala, Nahawanda Ahasanu; Auvaria, Shinfi Wazna; Nengse, Sulistiya (Al-Ard: Jurnal Teknik Lingkungan, 2018)
Muhammadiyah Babat Hospital in Lamongan District is one of the hospitals producing hazardous solid waste. Hazardous solid waste from the hospital has the potential environmental impacts and disrupt the public health both within the environment of the Hospital and surrounding communities, if not managed properly. Hazardous solid waste management system in the Hospital needs to be implemented properly and correctly in accordance with Government Regulation No. 101 of 2014 and KEPMENKES No.1204 / MENKES / SK / X / 2004. This research method using qualitative descriptive method by collecting primary and secondary data. Primary data obtained from observation and treatment in the field by weighing the quantity of hazardous solid waste and documentation of existing hazardous solid waste management, and interview. While secondary data obtained through study of literaturs and hospital documents related to the management of hazardous solid waste. The results showed that management system of hazardous solid waste at Muhammadiyah Babat Hospital was quite good and in accordance with Government Regulation and KEPMENKES. However, there are still some facilities that are not available to support the management of hazardous solid waste. Unavailable facilities include drainage channels, spill reservoirs, easily accessible APARs, and first aid facilities in the temporary landfill of hazardous solid waste in hospital. Suggestions that can be submitted to the conclusion of this research is the need for additional supporting facilities in temporary landfill of hazardous solid waste, in accordance with the applicable regulations, such as drainage channels, spill reservoirs, etc. Keywords: solid waste, hazardous solid waste, management, hospital.